2023
DOI: 10.3390/molecules28020601
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Spectroscopies of Nitrophenols and Nitrophenolates in Solution: From Electronic Dynamics and Vibrational Structures to Photochemical and Environmental Implications

Abstract: Nitrophenols are a group of small organic molecules with significant environmental implications from the atmosphere to waterways. In this work, we investigate a series of nitrophenols and nitrophenolates, with the contrasting ortho-, meta-, and para-substituted nitro group to the phenolic hydroxy or phenolate oxygen site (2/3/4NP or NP−), implementing a suite of steady-state and time-resolved spectroscopic techniques that include UV/Visible spectroscopy, femtosecond transient absorption (fs-TA) spectroscopy wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 112 publications
1
20
0
Order By: Relevance
“…In aqueous solution, a bathochromic shift is observed in the maxima of the absorption spectra analogous to experimentally measured absorption spectra (SI Figure S1). Nevertheless, both spectra computed with QM/MM and full TDDFT are red-shifted as compared to an experimentally measured absorption spectrum in aqueous solution . The difference between QM/MM and full TDDFT solvation is small, with an additional 9 nm redshift for the latter.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…In aqueous solution, a bathochromic shift is observed in the maxima of the absorption spectra analogous to experimentally measured absorption spectra (SI Figure S1). Nevertheless, both spectra computed with QM/MM and full TDDFT are red-shifted as compared to an experimentally measured absorption spectrum in aqueous solution . The difference between QM/MM and full TDDFT solvation is small, with an additional 9 nm redshift for the latter.…”
Section: Resultsmentioning
confidence: 77%
“…Most previous 4-NP studies were performed in solution and elaborated on the solvatochromic shift and pH dependence. Experimentally measured absorption spectra in aqueous solution located a maximum at 3.88 eV, 3.90 eV, or 3.91 eV. , Figure a summarizes the 4-NP absorption spectra calculated in this work. Whereas the absorption peaks at 3.81 eV in full TDDFT solvation, a reduced redshift as compared to the gas phase is obtained with QM/MM (maximum at 4.1 eV).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…All calculations were performed at T = 300 K. Values for Δ E and λ were obtained by geometry optimization of the TDDFT excited states in which the Tamm–Dancoff approximation (TDA) needed to be used to overcome issues with imaginary roots in full TDDFT optimizations. Though TDDFT has been shown to work well with small molecules, it is recognized that the accuracy of TDDFT in determining the geometries of excited states is less accurate than coupled-cluster singles and doubles (CCSD). , It is also recognized that full TDDFT often underestimates the stability of charge-transfer (CT) states, which are present in nitroaromatics, ,, though the use of TDA may help in this regard. , If CT states are present in 4NC, then the incurred errors will be directly dependent on the amount of CT character for each state …”
Section: Methodsmentioning
confidence: 99%
“…The photochemistry of nitrophenols and other nitroaromatics is commonly assumed to proceed through the excited triplet state manifold, based on the notion that they would exhibit similar photochemical characteristics to nitrobenzene . The earliest studies of nitrobenzene identified photoreduction products from photochemistry conducted in alcohol solutions, namely, 2-propanol, with evidence of hydrogen abstraction from 2-propanol as the likely reaction pathway. Similar conclusions have been extrapolated to many other nitrobenzene derivatives. No studies, however, have been able to definitively prove that the degradation of 4NC occurs via a direct reaction of its triplet state, leaving a possibility that photodegradation could occur through some other pathway such as charge or proton transfer in the excited singlet state manifold …”
Section: Introductionmentioning
confidence: 99%